PENGARUH CORPORATE GOVERNANCE, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP INTEGRITAS LAPORAN KEUANGAN - Anissa Oktafia, 12.05.52.0137; Poerwati, Rr. Tjahjaning (Students Journal of Accounting and Banking, 2016)
The purpose of this study was to examine institutional ownership, independent directors, audit committee, company size, and leverage the Integrity of Financial Statements. The population of this research are companies listed on the Indonesia Stock Exchange in 2009-2014. Samples were companies that follow the rating Governanace Corporate Perception Index (CGPI) 2009-2014. The sampling method using purposive sampling. To test and analyze the influence between variables using multiple linear regression analysis. The results show that institutional ownership and independent commissioners are not sgnifikan positive effect on the integrity of financial statements; audit committee significant positive effect on the integrity of financial statements; company size (size) significant negative effect on the integrity of financial statements; and leverage positive effect andÂ no significant the integrity of financial statements.Keywords:Â Corporate Governance, Institutional Ownership, Independent Commissioners, Audit Committee, Company Size, Leverage and Integrity of Financial Statements